2008
DOI: 10.1055/s-2008-1078727
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Prolonged Physical Training on the Pituitary Glucocorticoid Sensitivity Determined by Very Low Dose Intravenous Dexamethasone Suppression Test

Abstract: The activity of the hypothalamic-pituitary-adrenal axis is usually modulated by several stress factors, including exercise. Different responses are induced by physical training according to duration and intensity of exercise. During prolonged training, cortisol remains normal or decreased as a consequence of altered cortisol secretion, metabolism and excretion, and possibly by changes in glucocorticoid sensitivity. The aim of this study was to evaluate the impact of prolonged physical training on the glucocort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…In addition, we have shown that the pituitary glucocorticoid sensitivity is reduced during prolonged training [7]. The mechanisms responsible for the relative glucocorticoid resistance during prolonged exercise remains unknown but may involve modulation of target tissue expression of genes encoding the glucocorticoid receptor and/or other nuclear protein comodulators [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we have shown that the pituitary glucocorticoid sensitivity is reduced during prolonged training [7]. The mechanisms responsible for the relative glucocorticoid resistance during prolonged exercise remains unknown but may involve modulation of target tissue expression of genes encoding the glucocorticoid receptor and/or other nuclear protein comodulators [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…For example, dexamethasone inhibition of lipopolysaccharide‐induced IL‐6 was lower in trained compared with untrained men 35. In 18 male cadets in the Brazilian Air Force Academy, 6 weeks of intensive exercise training led to a reduction in basal cortisol levels, and in glucocorticoid receptor (GR) mRNA levels and decreased glucocorticoid sensitivity, measured as the response to intravenous low‐dose dexamethasone 45, 46. Binding capacity of GRs in peripheral blood monocytes was lower in semiprofessional soccer players than in young and older comparison subjects 47.…”
Section: Discussionmentioning
confidence: 99%
“…VLD-DST – are observed after the training program. Together, these observations suggest lower activity of the HPA axis with a reduction in the pituitary negative feedback to dexamethasone, possibly reflecting a more systemic reduction in GC sensitivity [33]. …”
Section: In Vivo Evaluation Of Gc Sensitivitymentioning
confidence: 99%